Disparities among The Baby Boomer, X, Y, And Z Generations regarding internet-based mental health literacy in Indonesia - Ayu Anulus; Yolly Dahlia; Danang Nur Adiwibawa; Lilik Hidayati (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Mental health literacy is important as the prevalence of mental health disorders increases, while access to information through digital media on the internet is becoming more widespread. With the different characteristics and patterns of internet consumption in each generation, the level of understanding of internet-based mental health information is expected to vary. This study aims to examine the differences in internet-based mental health literacy among the Baby Boomer, X, Y, and Z generations in Indonesia. Subjects and Method: This study uses a cross-sectional study method with an online survey involving 400 respondents from various generation groups in Indonesia. The independent variables were Baby Boomer, X, Y, and Z generations. The dependent variable was internet-based mental health literacy. Generational difference data was measured using a questionnaire and internet-based mental health literacy understanding was measured using a modified internet-based health literacy scale (eHEALS) questionnaire. The data were analyzed using the Kruskal-Wallis Test and the Mann-Whitney as the post hoc test. Results: The results of the study show that generation Z has a higher level of internet-based mental health literacy. The Kruskal-Wallis test shows that there is a statistically significant difference in internet-based mental health literacy between generations (p=0.025). The results of Mann-Whitney show that internet-based mental health literacy of baby boomers vs. generation X (p= 0.006) and baby boomers vs. generation Z (p=0.005) is significantly different. Conclusion: There are significant differences in internet-based mental health literacy between generations. These findings emphasize the importance of an intergenerational approach to online mental health education programs, so that information can be accessed and understood properly by all age groups.